Soil Properties in Natural Forest Destruction and Conversion to Agricultural Land,in Gunung Leuser National Park, North Sumatera Province - Basuki Wasis (Jurnal Manajemen Hutan Tropika, 2012)
Destruction of the Gunung Leuser National Park area of North Sumatera Province through land clearing and land cover change from natural forest to agricultural land. Less attention to land use and ecosystem carrying capacity of the soil can cause soil degradation and destruction of flora, fauna, and wildlife habitat destruction. Environmental damage will result in a national park wild life will come out of the conservation area and would damage the agricultural community. Soil sampling conducted in purposive sampling in natural forest and agricultural areas. Observation suggest that damage to the natural forest vegetation has caused the soil is not protected so that erosion has occurred. Destruction of natural forest into agricultural are as has caused damage to soil physical properties, soil chemical properties, and biological soil properties significantly. Forms of soil degradation caused by the destruction of natural forests, which is an increase in soil density (density Limbak) by 103%, a decrease of 93% organic C and soil nitrogen decreased by 81%. The main factors causing soil degradation is the reduction of organic matter and soil erosion due to loss of natural forest vegetation. Criteria for soil degradation in Governance Regulation Number 150/2000 can be used to determine the extent of soil degradation in natural forest ecosystems.